Rapid water temperature variations at the northern shelf of the Yellow Sea - L Asplin; F Lin; WP Budgell; Ø Strand (Aquaculture Environment Interactions, 2021)
During summer, there is great spatial variability in bottom water temperature on the northern shelf of the Yellow Sea. This variability is associated with a thermal front along the shelf. Oscillatory currents from semidiurnal and fortnightly period tides transport water masses laterally, resulting in oscillations of bottom water temperature at fixed positions, sometimes with large amplitudes. Temperature variations, as demonstrated in the present work, can cause damage to bottom-cultured scallops. In particular, in the scallop sea ranching area near Zhangzidao Island, such oscillations are evident in late summer. We constructed a spatial index of aggregated temperature variability from current model results identifying how temporal variability during the summer period varies in space. This information can be useful both in selecting favorable ranching areas and designing laboratory stress experiments on aquaculture candidate species.